METHODICAL WAYS OF DEVELOPING THE LANGUAGE OF PRE-SCHOOL CHILDREN - Nigora Avazovna Khidoyatova (Galaxy International Interdisciplinary Research Journal, 2023)
Problems encountered in the development of speech of preschool children.